Jurnalisme Konstruktif dalam Berita Varian Baru Covid-19 (Analisis Semiotika Roland Barthes terhadap Berita di Okezone.com) - Yudha Wirawanda; Kholif Huda Arrasyid (Calathu: Jurnal Ilmu Komunikasi, 2021)
The purpose of this study was to review the text of news related to the new variant of Covid-19. This was because in the midst of the Covid-19 pandemic news emerged related to new variants of the virus. The discussion focused on written news text related to the new variant of Covid-19 on the news portal okezone.com. This research used the concept of constructive journalism to analyze written news texts. The study used Roland Barthes semiotics to analyze the data. The result of this research was that some written news texts obtained some elements of constructive journalism. Keywords: constructive journalism, Covid-19, semiotics